Challenges in cost estimation under uncertainty: A case study of the decommissioning of Barsebäck nuclear power plant - Olav Torp; Ole Jonny Klakegg (Administrative Sciences, 2016)
Cost estimation is an important part of project planning. Over the years different approaches have developed, taking uncertainty into account in the cost estimation processes in order to tackle the dynamic nature of projects. However, when implementing these approaches, some challenges have been revealed. The aim in a cost estimation process is to establish a realistic overview of the total project costs and its uncertainties. Even though tools and methods for taking uncertainty into account are implemented, projects with cost overruns are often seen. In this paper we look into some challenges with the practice in cost estimation processes and identify possible improvements to overcome them. The purpose of this paper is to illustrate better solutions to some of the major weaknesses identified in current cost estimation practice. We use a case study of decommissioning of Barsebäck Nuclear Power Plant to illustrate how to overcome these challenges. First of all, this is an interesting case with challenges related to the project and the cost estimation process, given the complexity in the situation and that very few have experiences related to decommission of nuclear power plants. Second, we applied an approach that is not yet commonly used to develop cost estimates for this kind of projects. The paper concludes that it is possible to improve the results of uncertainty analysis of cost estimates. A well prepared process, with a suitable group of experts that go through a well-structured process, focusing both on risks and opportunities and using a top-down approach can compensate for some of the challenges related to cost estimation under uncertainty.
Keywords: 350; cost estimation; uncertainty analysis; decommissioning; nuclear power plant; group process